Demonstration Of Antigenic And Specific Outer Membrane Protein(S) Of Acinetobacter Baumannii - Shafiqul Islam, A.H.M. (2009)
Acinetobacter baumannii has been recognized as an emerging nosocomial pathogen and is very often multi-resistant to antibiotics. It has also been identified as an important cause of morbidity and mortality in hospitals, especially among immunocompromised patients. Acinetobacter baumannii dikenali sebagai bakteria penyebab penyakit nosokomial dan kebanyakannya adalah rintang terhadap pelbagai antibiotik. Ianya juga dikenalpasti sebagai penyebab utama kepada morbiditi dan kematian di hospital terutamanya bagi pesakit yang kurang imuniti terhadap penyakit.